Board of Directors Influence on Leverage: A Conceptual Perspective - Younas, Afshan; Kassim, Aza Azlina Md (International Journal of Applied Research in Management and Economics, 2020)
Board of directors are considered as an important proxy of corporate governance mechanism. Corporate governance plays a significant role in the development structure of stock market and businesses growth. In Gulf Cooperation Council region Oman is the first country to developed and adopt corporate governance mechanism. Oman holds a prominent position in the Middle East and North Africa region. The Omani economy basically depends on oil, gas and services sector. Due to oil crisis from 2015, Oman economy witnessed many challenges like rise in oil prices, unemployment and unfavorable balance of payment. On the other hand, the country encountered unfavorable debt level of the companies that made business companies unable to repay their loans. Therefore, this study proposes to explore conceptual model on the effect of board size, board composition and board tenure toward companies leverage. Though corporate governance mechanism is strong in developed countries, but the concept is still developing and progressing in Oman. Due to the current situation of Oman this study incorporates important proxies of corporate governance namely board structure, board composition and board tenure. Since the extensive research on corporate governance has been conducted but this relationship still not clearly established in developing countries specifically in context of Oman. Thus, this study provides a better and clear understanding on how the board size, board composition and board tenure impact and change capital leverage. In order to carry out this research, this study intended to collect secondary data from annual reports of listed companies at Muscat Securities Market. The discussions suggest the government and regulatory bodies’ that have strong corporate governance implication and practices may reduce the debt burden of the companies. The high proportion of leverage in capital structure may threaten the companies to bankruptcy or create negative image of firm in the financial market.